Pricing methods in outcome-based contracting: δ6: adherence-based pricing. (1st November 2020) - Alkhatib, Nimer S.; Slack, Marion; Bhattacharjee, Sandipan; Erstad, Brian; Ramos, Kenneth; McBride, Ali; Abraham, Ivo
Abstract: Aims: Six Delta is a six-dimensional independent platform for outcome-based pricing/contracting. The sixth dimension (δ6) estimates prices on the basis of adherence to the prescribed regimen, whereby manufacturers provide payers with adherence-enhancing programs and whereby payers implement these programs and provide adherence data to the manufacturer. We describe this dimension's methodology and present a proof-of-concept application to the treatment of non-small cell lung cancer (NSCLC) with EGFR mutation with osimertinib. Materials and methods: We propose two paybacks based on adherence: in-advance (based on clinical trial data) and in-arrear (based on real-world data). The risk of efficacy failure pricing dimension utilizes a 7-step method: 1) defining efficacy endpoints; 2) extracting data; 3) predicting models; 4) estimating in-advance and in-arrear paybacks; 5) suggesting ranges for in-advance and in-arrear paybacks; 6) adjusting for medical inflation; and 7) performing Monte Carlo Simulation (MCS) to estimate the DSPAdherence . A proof-of-concept exercise with osimertinib in NSCLC was performed for two hypothetical outcome-based contracts: 1-year (2019–2020) and 2-year (2019–2021). The 2018 wholesale acquisition cost (WAC) for a 30-day prescription was used and inflated as needed. Herein, the DSPAdherence is estimated exclusively in terms of in-advance payback because real-world data about osimertinib are not yet available and thus the in-arrear payback cannot yet be estimated. Results: For the 1-year contract, the average price for osimertinib was $13, 798 (SD=$1, 265) and the DSPAdherence was $13, 785 (or −5.69% of the 2018 WAC) for a 30-day prescription. For the 2-year contract, the average price was $12, 555 (SD=$2, 847) and the DSPAdherence was $12, 582 (or −13.92% of the 2018 WAC). Conclusions: We demonstrated that adherence-based pricing methods can be integrated into our proposed Six Delta platform for outcome-based pricing/contracting. The proof-of-concept exercise needs to be expanded with the in-arrear pricing method based on real world data to be secured.